Uji Efek Inokulan Pelet dan Kapsul Trichoderma harzianum terhadap Kandungan Resin dalam Kayu Gaharu Pada Lahan Berbeda - Mega, I Made; Kartini, Ni Luh; Suranjaya, I Gede (Agrotrop : Journal on Agriculture Science, 2024)
Testing the Effect of Trichoderma harzianum Pellet and Capsule Inoculant on Resin Content in Agarwood Wood on Different Lands. Resin is a secondary metabolite compound produced by agarwood plants due to injury or infection by microbes. The formation of gaharu resin is influenced by the genetics of the resin-producing tree, the type of inducing microbe, the environment and the length of the resin formation process in gaharu. Previous research showed that inoculant pellets and Trichoderma harzianum mushroom capsules could increase the resin content in agarwood in the Dauhpuri Marga Village experimental garden. This research aims to prove the effect of inoculant in Trichoderma harzianum mushroom pellet and capsule packaging on the resin content in agarwood in several different fields. This research is an experimental research with a factorial pattern RCB design. The first factor is the type of inoculant packaging with 3 levels, namely: F0 (without inoculant), Fp (pellet inoculant), Fk (capsule inoculant). The second factor is land type consisting of 3 levels: Kl (Klungkung), Mg (Marga), Sl (East Selemadeg). The parameters observed were: color of agarwood, aroma of agarwood, resin content in agarwood. Quantitative data from observations/measurements are analyzed statistically using variance analysis, if significant occurs, it is continued with the Duncan Test. The research results showed that the type of inoculant packaging had a significant effect on the resin content in agarwood, but the type of land had no significant effect on the resin content in agarwood. This proves that Trichoderma harzianum fungus pellet inoculant can increase the resin content in agarwood on various different fields.